’Is We Carnival Culture; is We Caribbean Thing; is We Life!’: Demystifying Gendered Relations and the Taboo of Sex and HIV and AIDS among West Indian Women - Shivaughn Hem-Lee-Forsyth (Recent Trends in Arts and Social Studies Vol. 3, 2023)
This study covers the critical and interconnected roles of several socio-cultural issues in the Caribbean: Patriarchy, sex commercialisation, men having sex with men, violence, and religious practices - all contributing to HIV and AIDS risk. By doing so, the article promotes awareness of the harsh realities of Caribbean women’s sexual lives and how Caribbean culture disproportionately exposes them to HIV and AIDS risk. The report concludes with a need for more research into the crucial socio-cultural factors that negatively influence male-female relationships and their effect on HIV and AIDS risk in the Caribbean.